HARMONISASI BUKU III KITAB UNDANG-UNDANG HUKUM PERDATA DENGAN Convention on Contracts for the International Sales of Goods dan United Nation Commission on International Trade Law TERHADAP KONTRAK DAGANG INTERNASIONAL - , Chrisstar Dhini, Novika Maharani, Reza Amarulloh (PRIVAT LAW II, 2015)
AbstractAs the development of globalization, business transactions also started to spread across the country that was born the international trade contract at the initiative of the parties. But in practice it is necessary to choice of law in the resolution of disputes in which the parties involved have a different nationality to the legal system of each vulnerable dispute. Therefore, the international community began to adopt a system of laws and regulations that can be applied in the transaction parties. So the role of national law and the law governing the trading iternasional becomes important. It became the forerunner to the establishment of the International pour I âUnification du Droit (UNIDROIT), which was formed with the aim of unification and harmonization of international law which is now selling its successor is the United Nations Commission on International Trade Law (UNCITRAL). UNCITRAL became a specialized agency that handles international trade also resulted in the United Nations Convention on International Sales of Goods 1980 (UNCISG) and additional regulations are followed. As international law UNCITRAL and UNCISG used as a benchmark for the Indonesian government to establish regulations on international trade in particular. National law concerning own trading Indonesia based on Book III Code Civil (Civil Code). In which there is harmonization between UNCITRAL and UNCISG with Book III of the Civil Code, especially in the concept and principles of contract completion.Keywords: contract law international trade, UNCITRAL, UNCISG